Estudo da difusividade térmica de compósitos biocompatíveis, materiais magnetocalóricos, e intermetálicos via sinal fotoacústico traseiro - Mariucci, Vinícius Vaulei Gonçalves (2014)
It was investigated the effective thermal diffusivity behavior for biocompatible composites made of hydroxyapatite (HAp) and niobium pentoxide (Nb2O5) powders before, and after sinterization at 1000 °C. Then, it was studied the phase transitions for temperature variations in process of heating and cooling of a sample of gadolinium (Gd) and a sample of nickel-titanium (NiTi or Nitinol) through thermal diffusivity. For the magnetocaloric sample (Gd) it was detected the transition between ferromagnetic paramagnetic phases around a Curie temperature of TC = 18 °C, being a transition of second order (without latent heat). Also for the intermetallic alloy of NiTi it was possible to observe the structural transitions between martensite austenite phases (in this cases, a transition of first order related to a latent heat). The results for the thermal diffusivity of the Nitinol revealed the characteristic temperatures observed for the two phases, like the initial temperature (As = 50 °C) and final temperature (Af = 80 °C) for austenite phase transition, and the inicial temperature (Ms = 45 °C) and final temperature (Mf = 25°C) for martensite transformation. With thermal cycling it was clearly observed an absence of thermal hysteresis for the magnetocaloric sample. However the same doesn't occur with the NiTi alloy, which presents an hysteresis of about 5 °C between As and Ms. The values obtained for the thermal diffusivities, and the behaviors observed for the samples of Gd and NiTi agree nicely with the values and the patterns reported in the literature.